GAWMerge expands GWAS sample size and diversity by combining array-based genotyping and whole-genome sequencing - Mathur, Ravi; Fang, Fang; Gaddis, Nathan; Hancock, Dana B.; Cho, Michael H.; Hokanson, John E.; Bierut, Laura J.; Lutz, Sharon M.; Young, Kendra; Smith, Albert V.; Silverman, Edwin K.; Page, Grier P.; et al. (Communications biology, 2022)
Genome-wide association studies (GWAS) have made impactful discoveries for complex diseases, often by amassing very large sample sizes. Yet, GWAS of many diseases remain underpowered, especially for non-European ancestries. One cost-effective approach to increase sample size is to combine existing cohorts, which may have limited sample size or be case-only, with public controls, but this approach is limited by the need for a large overlap in variants across genotyping arrays and the scarcity of non-European controls. We developed and validated a protocol, Genotyping Array-WGS Merge (GAWMerge), for combining genotypes from arrays and whole-genome sequencing, ensuring complete variant overlap, and allowing for diverse samples like Trans-Omics for Precision Medicine to be used. Our protocol involves phasing, imputation, and filtering. We illustrated its ability to control technology driven artifacts and type-I error, as well as recover known disease-associated signals across technologies, independent datasets, and ancestries in smoking-related cohorts. GAWMerge enables genetic studies to leverage existing cohorts to validly increase sample size and enhance discovery for understudied traits and ancestries. GAWMerge is a computational tool that allows users to integrate SNP genotyping data from array techniques or whole-genome sequencing, providing a feasible method to leverage existing cohorts to increase sample size in genetic studies.